2015
DOI: 10.18632/oncotarget.5539
|View full text |Cite
|
Sign up to set email alerts
|

Expression of young HERV-H loci in the course of colorectal carcinoma and correlation with molecular subtypes

Abstract: Conclusion: These results suggest a functional role of HERV-H sequences in colorectal carcinogenesis. The pronounced connection with microsatellite instability warrants a more detailed investigation. Thus, HERV-H sequences in addition to tumor specific mutations may represent clinically relevant, truly CRC specific markers for diagnostic, prognostic and therapeutic purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 48 publications
(62 reference statements)
2
53
0
1
Order By: Relevance
“…The most well established epigenetic changes are promoter hypermethylation and associated silencing of tumor suppressor genes [95, 99, 100] as well as genome-wide DNA hypomethylation [101103]. Hypomethylation of ERVs and L1s in many tumors has been documented [104106] and general transcriptional up-regulation of ERVs and L1s is often observed in cancers [33, 107109]. However, other studies have shown no significant changes in ERV expression in selected human cancers compared to corresponding normal tissues [110, 111].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most well established epigenetic changes are promoter hypermethylation and associated silencing of tumor suppressor genes [95, 99, 100] as well as genome-wide DNA hypomethylation [101103]. Hypomethylation of ERVs and L1s in many tumors has been documented [104106] and general transcriptional up-regulation of ERVs and L1s is often observed in cancers [33, 107109]. However, other studies have shown no significant changes in ERV expression in selected human cancers compared to corresponding normal tissues [110, 111].…”
Section: Introductionmentioning
confidence: 99%
“…Expression of HERV-H itself and LTR7-driven chimeric long non-coding RNAs is a noted feature of embryonic stem cells and normal early embryogenesis, where several studies indicate an intriguing role for this ERV group in pluripotency (for recent reviews see [8, 10, 60]). A few studies have also noted higher general levels of HERV-H transcription in colon cancer [109, 135]. The LTR7-driven isoform of SLCO1B3 makes a truncated protein lacking the first 28 amino acids but also includes protein sequence from the LTR7 and an adjacent MER4C LTR (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…98,99 A major consequence of the abundance of LTR regulatory elements within the human genome is that permissive HERVs reactivations are often associated with pathological context including cancer. 100 The overall data present in literature regarding an association between HERVs expression pattern and colon cancer are rather in accordance and the majority of the scientific reports is focused on HERV-H family and colon cancer. 101,102 HERV-H and colon cancer.…”
Section: Hervs and Colon Cancermentioning
confidence: 85%
“…The authors concluded that this protein may serve as a target for antitumor therapy. In a large-scale analysis of 139 colon cancer samples and adjacent normal tissue pairs, Pérot et al, 100 about 10 years later, confirmed the expression of the HERV-H Xp22.3 transcripts in half of the analyzed tumor samples (70/139). Furthermore, HERV-H expression patterns were assessed with regard to clinical parameters and molecular features of the cancer, showing a strong correlation between HERV-H expression and the microsatellite instable (MSI) tumor as well as lymph node invasion of the tumor cells.…”
Section: Hervs and Colon Cancermentioning
confidence: 91%
“…В частности при КРР показана экспрессия генов эндогенных ретровирусов HERV-E и HERV-H, причем экспрессия генов HERV-H отмеча-лась в период прогрессирования заболевания и корре-лировала с микросателлитной нестабильностью генома опухолевых клеток и инвазией ими лимфатических узлов вне зависимости от возраста пациентов, локали-зации и градации опухоли и мутаций в ее геноме. Это послужило основанием рассматривать экспрессию ге-нов HERV-H в качестве нового маркера КРР [49].…”
Section: Introductionunclassified